Refractoriness to anaphylactic shock after continuous feeding of cow's milk to guinea-pigs. - Coombs, R R (1978)
Further studies have been undertaken on the anaphylactic sensitization to cows' milk in guinea-pigs given cows' milk to drink instead of water. With continuous feeding over a prolonged period of time (over 70 days), about 70% of the guinea-pigs became refractory to intratracheal challenge of cows' milk and about 30% to intravenous challenge. Some guinea-pigs given cows' milk from the second day of life appeared not to undergo an early sensitization at all and may have been displaying a tolerance to anaphylactic sensitization. The degree to which this was shown may be genetic. The anaphylactic sensitivity, particularly as regards intravenous challenge, could be assessed by examining the sera for IgGl a antibodies to cows' milk by passive cutaneous anaphylaxis.